New face of Journal of Medical Physics and Biophysics: a reflection of new spirit from a new organization - Supriyanto Ardjo Pawiro (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2016)
The meeting in Yogyakarta in November 2015 marked a new chapter of Medical Physics educational, scientific, and professional development in Indonesia; a new professional body, declared as Indonesian Association of Physicists in Medicine, was born a result of unification between Indonesian Medical Physics and Biophysics Association and Indonesian Medical Physicists Association. This long-awaited milestone was reached as a mutual agreement and recognition between the founders, prominent figures, and members of the two groups of medical physicists, academia, and scientists. The unification was followed by a major re-organization during which a new committee with a set of new people was involved in setting new foundations of the newborn organization. This great labor includes also a setting of a new board responsible for scientific publications, reflected on the change of JMPB’s look and how it runs. In this issue, readers and authors of JMPB might have noticed some change in the face and looks in the articles—the layout, the cover, and the structure. Whereas the journal previously accommodates medical physics-related sections of Diagnostic and Interventional Imaging, Radiation Therapy, Nuclear Medicine, Experimental Biophysics, and Computational Biophysics, the new format introduces new sections of Radiological Protection, and Review Article, enabling a broader possibility of research scope published in JMPB. These new arrangements, however, is made complex with the shift of technical team members working behind the screen, causing a major delay in article processing. To add to that extent, JMPB also experienced a catastrophic technical issue on our web server, which has not been resolved until recently. Therefore, I believe it is both timely and appropriate to extend the team’s sincere apologies for any inconvenience caused. I, now, in the new spirit as new as the new look of the journal, encourage more submissions to JMPB for a wider audience, and to support this new organization facing its new dawn.